Rising national income per worker and falling real wages in the Philippines in the 1970s - Oshima, Harry T.; De Borja, Elizabeth; Paz, Wilhelmina (1986)
One of the unsettled issues in Philippine economic development is the decline in real wages per worker while GNP/national income per worker was rising. This divergence in the Philippines is unusual in the postwar experience Asia as in both Taiwan and South Korea, growth was accompanied by rising real wages in agriculture and industry, even when there was considerable unemployment. The paper is divided into two sections. In the first part, the statistics of national product and real wages are discussed. In the second part, three hypotheses are examined. The first deals with the labor supply side, the second with labor demand and the last is about prices and money supply aspects. High underemployment rates in the '70s coupled with the rapid growth of the labor force due to relatively high population growth rates and increasing labor force participation rates especially of women may have exerted a downward pressure on real wages. This was aggravated by the slow growth of productivity per worker in the agricultural sector. On the other hand, the urban industrial sector did not perform as expected and failed in terms of employment generation to some extent due to government policies which were largely distortionary. Although some degree of growth was achieved, it was not as impressive compared to that of other Asian countries and was attained at the expense of labor.
Philippine Review of Economics and Business (formerly The Philippine Review of Business and Economics)
Includes bibliographical references.
Keywords: Wages -- Philippines; National income -- Philippines; Labor supply -- Statistics